Proceedings of the 13th Workshop in Primary and Secondary Computing Education 2018
DOI: 10.1145/3265757.3265761
|View full text |Cite
|
Sign up to set email alerts
|

Comparing K-5 teachers' reported use of design in teaching programming and planning in teaching writing

Abstract: K-5 teachers teach a range of subjects & develop generic teaching skills; when starting to teach computing, particularly programming, practitioners may not realise that they can draw on these other skills to support their teaching. In a small study of K-5 teachers, potential synergies were suggested between using planning in the the teaching of writing and design in the teaching of programming. In this paper, we explore these synergies by surveying a wider group of teachers (n=207) on their uses of planning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Why is hard to fathom. Confidence in teaching programming is the only other difference we have related to gender, with males more confident to teach programming than females (Waite et al, 2018b) . However, there was no statistically significant difference for the selection of terms for any image by confidence.…”
Section: Gendermentioning
confidence: 96%
See 3 more Smart Citations
“…Why is hard to fathom. Confidence in teaching programming is the only other difference we have related to gender, with males more confident to teach programming than females (Waite et al, 2018b) . However, there was no statistically significant difference for the selection of terms for any image by confidence.…”
Section: Gendermentioning
confidence: 96%
“…Added to this, few K-5 teachers in England are thought to have been taught programming or design themselves, therefore further research, support and training have been called for (The Royal Society, 2017a). Recent research suggests teachers in England think design is useful but avoid doing it (Waite et al, 2018b) . However, there has been no research to understand the reasons behind this.…”
Section: Design In Programmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Armoni (2013) renamed the object level as algorithm; using this Statter and Armoni (2016) evidenced impact on programming progress from high school students who understood the level at which they were working at. Another study using this framework reported teachers of K-6 students supporting learners to move between the LOA levels in teaching programming in similar ways to how they supported young students in learning how to write in English lessons (Waite, Curzon, Marsh, and Sentance, 2018). Related to this work is the Abstraction Transition Taxonomy (ATT) (Cutts, Esper, Fecho, Foster, and Simon, 2012).…”
Section: Levels Of Abstractionmentioning
confidence: 99%